Women's Political Participation in Post-conflict Settings: The Case of Timor-Leste. Issue 2 (3rd April 2022) - Niner, Sara; Cummins, Deborah; Sahin, Selver B.; Mulder, Stella; Morrison, Emily
ABSTRACT: Tackling gender gaps in political representation is a key pillar of peace building and development interventions in conflict-affected environments, which has been addressed using special measures (e.g., gender quotas and reserved seats). We argue that although this is a necessary first step, these interventions privilege descriptive or quantitative indicators that may not equate to the substantive participation of women. Instead, a focus on qualitative transformation of deeply entrenched inequitable social structures is required. Our argument is illustrated by the case study of Timor-Leste, where control of political institutions is held by a small group of privileged, male leaders, legitimised by a rigidly defined social hierarchy. We argue that any special measures need to be accompanied by social change that provides equality of opportunity for participants within political parties, political institutions and electoral systems. By providing this analysis the article aims to contribute to the discussion of the ways in which gendered structural limitations can be better identified and addressed to promote more effective participation by women in politics in post-conflict settings.